Uso de nociones musicales para el desarrollo socio afectivo en los niños del subnivel inicial 2 - Roca Hernández, Martha Elizabeth (2021)
The present research is focused on the realization of an educational product for initial education teachers on the use of musical notions that can be given within the teaching and learning methods, showing its importance in the methodological processes for the integral formation of boys and girls from 3 to 5 years old, in addition to designing innovative strategies that support the use of this resource as a medium in education. Based on the principle of mother tongue, music teaches through play and directly involves the development of skills. Respecting the harmony of assimilation of the child, allowing him to discover, experiment and develop his musical sensitivity. On the other hand, musical methods and theories will be shown through which this use will be oriented in initial education that allows the holistic development of boys and girls at a socio- affective and motor level. Finally, in this benefit, activities will be planned in which music is used as a methodological strategy in which various contents and themes to be developed in the teaching of initial education will be worked on, complementing music as a didactic resource that will go especially with selected songs for musical work in this first educational stage. This work aims to balance the benefits and importance of the use of music in the development of children from 3 to 5 years of age, and the application of music education in their lives, providing didactic methodologies and educational strategies that help the teacher in his work as a guide for the acquisition of new knowledge in boys and girls.